# Prove that<

Let Δ =

Applying Row Transformations

R2 R2 – R1

Δ =

R3 R3 – R1

Δ =

Taking (β – α)(γ – α) from R2 and R3 respectively

Δ = (β – α) (γ – α)

Applying R3 R3 – R2, we have

Δ = (β – α) (γ – α)

Expanding along R3, we have

Δ = (β – α) (γ – α) [0 (α2 × (-1) – (β + γ) × (β + γ) – (γ – β)((-1) × α – 1 × (β + γ) + 0 (α × (β + γ) – 1 × α2)

Δ = (β – α) (γ – α) [0 – (γ – β)( - α - β – γ) + 0]

Δ = (β – α) (γ – α) (γ – β) (α + β + γ)

Δ = (α – β) (β – γ) (γ – α) (α + β + γ)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Prove the followiMathematics - Board Papers